Development of a new tool for the long term in vitro ecotoxicity testing of nanomaterials using a rainbow-trout cell line (RTL-W1). (August 2018) - Galbis-Martínez, L.; Fernández-Cruz, M.L.; Alte, L.; Valdehita, A.; Rucandio, I.; Navas, J.M.
Abstract: The current wide use of manufactured nanomaterials (MNs) is leading to the release of nanoparticles (NPs) to water bodies. Aquatic organisms, including fish, are exposed to low concentrations of NPs for long periods of time being necessary to develop laboratory toxicity tests reflecting realistic conditions. Additionally, today there is a demand of in vitro assays respecting the 3Rs principle. Thus, the main aim of this work was to stablish an in vitro tool for the assessment of long-term NPs ecotoxicity. Considering the key role of liver in detoxification, a rainbow trout liver cell line, RTL-W1, was used. CuO NPs were chosen to validate this tool taking into account their important production level. Cells were exposed for 21 days to 25 or 100 μg CuO NPs/ml. Every seven days cells were split and one fourth of them transferred to a new plate with appropriate concentrations of NPs in culture medium. Lower concentrations of CuO NPs did not cause any deleterious effect, whereas higher concentrations led to significant mortality after 14 days and to the intracellular accumulation of Cu particles. Identical results were observed in cells exposed to CuSO4 at the same Cu concentrations. Therefore, the observed toxic effects might be mainly due to Cu 2+ ions. Highlights: Development of a tool for nanomaterials long-term ecotoxicity assessment in vitro RTL-W1 cells were exposed to CuO NPs for 21 days at 24 h EC10 and EC50. CuO NPs dissolved quickly being not detectable after six days exposure. Lower concentrations did not induce toxicity but a long-term increased toxicity was observed with higher concentrations. Similar results were detected after exposure with CuSO4 suggesting that toxic effects were probably due to ionic fraction.